The Impact Of Foreigners In Enhancing Speaking Ability Of Bracelet Sellers At Kuta Beach - Muh Hamburabbi; Miptahulloh Ali Ilham; M. Fahrurrozi; Ali Alfian Amrin; Moh. Irpan (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The objective of this article was to investigate the impact of foreigners on encouraging the speaking ability of child bracelet sellers at Kuta Beach. This research implemented a qualitative descriptive design taken by purposive sampling. There are 7 participants in this research and they are child bracelet sellers at Kuta Mandalika Beach, Lombok. Observations, interviews and documentation are used to gather the data. The finding of this research shows that foreigners are very helpful in enhancing the speaking ability of child bracelet sellers at Kuta Beach because they can interact directly and practice English with people who make English their mother tongue and second language. Therefore, they quickly absorb vocabulary and phrases that can improve their English skills.